Adhesive Films from Dopamine‐Functionalized Polydimethylsiloxane Polymer Conetworks. Issue 8 (15th February 2023) - Mugemana, Clément; Mertz, Grégory; Grysan, Patrick; Dieden, Reiner; Ruch, David
Abstract: Polydimethylsiloxane (PDMS) adhesive films have increasingly attracted attention due to their inherent properties such as biocompatibility, high flexibility, optical transparency, and many others. In this contribution, dopamine‐functionalized polydimethylsiloxane polymer conetworks prepared from poly(pentafluorophenyl acrylate)‐l‐polydimethylsiloxane (PFPA‐l‐PDMS) amphiphilic polymer conetwork precursors are proposed. This straightforward approach gives easy access to polydopamine‐functionalized PDMS polymer conetworks with a different composition, stiffness of the polymer conetwork, and their corresponding nanoscale phase‐separated morphologies. The adhesive property of the polymer films on the glass substrate obtained by lap shear testing gives a maximum adhesive strength of 0.85 ± 0.08 MPa thanks to phase‐separated morphologies at the nanometer scale and the high flexibility inherent to polysiloxane. The proposed approach provides an easy and straightforward way to introduce dopamine into a polymer conetwork with tunable adhesive properties. Abstract : Adhesive films prepared from polydopamine‐functionalized polydimethylsiloxane polymer conetworks with tunable stiffness and nanoscale phase‐separated morphologies are presented.